THREE-DIMENSIONAL SIMULATION OF TIDAL CURRENT IN LAMPUNG BAY: DIAGNOSTIC NUMERICAL EXPERIMENTS - Alan Frendy Koropitan; Safwan Hadi; Ivonne M.Radjawane (International Journal of Remote Sensing and Earth Sciences, 2006)
Princeton Ocean Model (POM) was used to calculate the tidal current in Lampung Bay using diagnostic mode. The model was forced by tidal elevation, which was given along the open boundary using a global ocean tide model-ORITIDE. The computed tidal elevation at St. 1 and St 2 are in a good agreement with the observed data, but the computed tidal current at St 1 at depth 2 m is not good and moderate approximation is showed at depth 10 m. Probably, it was influenced by non-linier effect of coastal geometry and bottom friction because of the position of current meter, mooring closed to the coastline. Generally, the calculated tidal currents in all layers show that the water flows into the bay during flood tide and goes out from the bay during ebb tide. The tidal current becomes strong when passing through the narrow passage of Pahawang Strait. The simulation of residual tidal current with particular emphasis on predominant contituent of M2 shows a strong inflow from the western part of the bay mouth, up to the central part of the bay, then the strong residual current deflects to the southeast and flows out from the eastern part of the bay mouth. This flow pattern is apparent in the upper and lower layer. The other part flows to the bay head and froms an antic lockwise circulation in the small basin region of the bay head. The anticlockwise circulations are showed in the upper layer and disappear in the layer near the bottom.